2019
DOI: 10.3389/fpsyt.2019.00275
|View full text |Cite|
|
Sign up to set email alerts
|

Nerve Growth Factor Serum Levels Are Associated With Regional Gray Matter Volume Differences in Schizophrenia Patients

Abstract: Numerous neuroimaging studies have revealed structural brain abnormalities in schizophrenia patients. There is emerging evidence that dysfunctional nerve growth factor (NGF) signaling may contribute to structural brain alterations found in these patients. In this pilot study, we investigated whether there was a correlation between NGF serum levels and gray matter volume (GMV) in schizophrenia patients. Further, we investigated whether there was an overlap between the correlative findings and cross-sectional GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 140 publications
2
9
0
1
Order By: Relevance
“…As described previously, we found significant reductions of grey matter volume in schizophrenia patients in a widespread fronto-temporo-parietal network (44).…”
Section: Regional Grey Matter Volumes and Their Correlations With Bdnsupporting
confidence: 86%
See 1 more Smart Citation
“…As described previously, we found significant reductions of grey matter volume in schizophrenia patients in a widespread fronto-temporo-parietal network (44).…”
Section: Regional Grey Matter Volumes and Their Correlations With Bdnsupporting
confidence: 86%
“…The study protocol was approved by the institutional review board of RWTH Aachen University Hospital, Aachen, Germany. A total of 20 healthy volunteers (12 male and 8 female) recruited from the local community and 19 patients with schizophrenia (11 male and 8 female) recruited at the Department of Psychiatry, Psychotherapy, and Psychosomatics, RWTH Aachen University Hospital, were enrolled in this study, as, in part, previously reported by Neugebauer and colleagues (44). Two of the patients had to be excluded due to abnormalities in their MRI data sets (one because of grossly enlarged lateral ventricles, most likely due to infantile hypoxia, and another one due to technical artifacts).Written informed consent was given by all participants prior to inclusion.…”
Section: Subjectsmentioning
confidence: 99%
“…BDNF may therefore contribute to observed brain volume reductions in schizophrenia, especially in regions of significant BDNF function such as the hippocampal and frontal regions. It is likely, however, that BDNF works synergistically with other neurotrophins, growth factors, and immune response parameters that have similarly shown associations with frontal and hippocampal volume [68][69][70]. The current meta-analysis adds to existing evidence of the status of BDNF as a biomarker of schizophrenia with multiple pleiotropic effects including the incidence of the illness, predisposing factors, cognitive functions, and clinical status [37,50,[71][72][73][74][75][76][77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, there are acute-phase proteins, anti-inflammatory proteins, macrophage and lymphocyte pro-inflammatory factors, including cytokines and chemokines of cells of natural and adaptive immunity. These deviations from the normal status can be combined in various ways to create numerous immune patterns affecting the signaling and metabolic pathways in the periphery and in the brain [ 14 ]. On this general background, the immune profiles of patients with schizophrenia with severe negative symptoms have not been studied enough.…”
Section: Introductionmentioning
confidence: 99%